PENANAMAN NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM MEMBENTUK AKHLAK PESERTA DIDIK - suprihatin suprihatin (Sosial Budaya, 2015)
The diversity of Indonesian society is a logical consequence of the laws of nature (natural law, the laws), something natural. In this, the diversity of Indonesian society is the need for education on multicultural education. Multicultural education is defined as a social policy based on the principles of cultural maintenance and have a mutual respect among all cultural groups in society. Multicultural education is a process that can be defined as the process of developing an attitude and code of conduct of a person or group of people in a mature business man through the efforts of teaching, training, processes, actions, and ways of educating that respects plurality and heterogeneity are humanistic. Principles of national education, as embodied in Chapter III, Article 4, paragraph 1: 'Education held in a democratic and fair and not discriminatory to uphold human rights, religious values, cultural values, and the diversity of the nation. In the Islamic perspective, multicultural education that the principle of democracy, equality, and justice has turned out to be compatible with Islamic doctrines and historical experience of Muslims. Education is a process of transmitting culture and learning at the same societal norms, through certain methods so that people acquire the knowledge, understanding, and how to behave in accordance with needs.